Effects of airflow distribution changes on the thermal environment of IT equipment in data centers - Wei Lun Wang; Yichen Li; Kuei-Peng Lee (Case Studies in Thermal Engineering)
The layout of IT equipment racks in data centers directly affects airflow circulation. Inefficient airflow or uneven cooling can lead to thermal shutdowns, compromising data centers’ IT equipment operational stability and air-conditioning system efficiency. Precise control of environmental parameters can prevent localized hotspots and airflow mixing, which are crucial for maintaining effective cooling. The distribution of cold and hot air determines the effectiveness of data center cooling; greater mixing of hot and cold air results in greater energy loss. Effective airflow management and optimization of air-conditioning energy use are crucial to preventing short airflow circuits between racks and minimize heat diffusion. This study was conducted at a data center in a financial information building in Taipei, Taiwan. The data center had an area of approximately 117 m2. Computational fluid dynamics simulations were performed to analyze airflow channel configurations, specifically cold and hot aisle containment systems, with validation through actual measurements. The study also examined airflow distribution inside and outside IT equipment racks. Models of rack frames and equipment chassis were developed, and the effects of side panels between racks were investigated. Four simulated scenarios were considered, varying airflow channel enclosures and the installation of side panels between modular racks. These configurations were simulated using ANSYS software with clearly defined quantitative boundary conditions to assess their effects on data center cooling effectiveness. The study concluded that an overhead hot aisle enclosure configuration without side panels between racks substantially enhances heat dissipation from IT equipment and improves overall data center cooling effectiveness.